Després de la modernitat: el cinema d’Albert Serra - Àngel Quintana (Catalonia)
Albert Serra’s cinema captures certain characteristics of modernity, but it is a cinema that was born when this modernity entered into crisis and seems to find new ways in digital cinema. Located on the border between contemporary art and auteur cinema, between the avant-garde and the cult of tradition, Albert Serra has become a paradigm of the new contemporary author capable of finding a singular aesthetic from the air of time. The theme that unites the six feature films in his filmography is none other than the persistence of myth. The literary resonances of the figure of the myth allow him to show a series of archetypal figures lost in a situation of transit, in which presences are more important than dramatic gestures and movements only draw vanishing lines in front of certain landscapes that at times seek a way to achieve a certain abstraction of figuration.